Korelasi Supervisi Akademik terhadap Kompetensi Pedagoik Guru Taman Kanak-Kanak Kecamatan Bergas Kabupaten Semarang - Maslihah, Nur Isna; Wuryandini, Endang; Nurkolis, Nurkolis (Jurnal Inovasi Pembelajaran di Sekolah, 2024)
Pedagogical competency problems that are often encountered are teachers who are considered unable to manage learning optimally, design and implement learning, evaluate learning outcomes, and develop students' potential as well as difficulties in using learning technology. The aim of this research is to determine the correlation between academic supervision and teacher pedagogical competence. The research approach used is quantitative research and uses descriptive analysis methods The sample for this research was 89 teachers selected by proportional random sampling at each school. Validity, reliability and regression requirements tests, single regression and multiple regression tests using the SPSS for Windows version 23 program. The results of the anova test of academic supervision on pedagogical competence obtained a significance value of 0.000 which is smaller than the significance level of 0.05 or 0.000 < 0.05. Meanwhile, the Fcount value of 95.297 is greater than the Ftable value at a confidence level of 0.05, namely a value of 3.95 or 95.297 > 3.95. Based on these results, the hypothesis which states that there is a correlation between academic supervision and the pedagogical competence of kindergarten teachers in Bergas District, Semarang Regency is accepted. . The findings from research on academic supervision have a positive correlation and have a significant effect on teacher pedagogical competence, amounting to 52.3%, the remainder is influenced by other variables.